Requirements for chromatin modulation and transcription activation by the Pho4 acidic activation domain. - McAndrew, P; Svaren, J; Martin, SR; Hörz, W; Goding, C (1998)
Perhaps the best characterized example of an activator-induced chromatin transition is found in the activation of the Saccharomyces cerevisiae acid phosphatase gene PHO5 by the basic helix-loop-helix (bHLH) transcription factor Pho4. Transcription activation of the PHO5 promoter by Pho4 is accompanied by the remodeling of four positioned nucleosomes which is dependent on the Pho4 activation domain but independent of transcription initiation. Whether the requirements for transcription activation through the TATA sequence are different from those necessary for the chromatin transition remains a major outstanding question. In an attempt to understand better the ability of Pho4 to activate transcription and to remodel chromatin, we have initiated a detailed characterization of the Pho4 activation domain. Using both deletion and point mutational analysis, we have defined residues between positions 75 and 99 as being both essential and sufficient to mediate transcription activation. Significantly, there is a marked concordance between the ability of mutations in the Pho4 activation domain to induce chromatin opening and transcription activation. Interestingly, the requirements for transcription activation within the Pho4 activation domain differ significantly if fused to a heterologous bHLH-leucine zipper DNA-binding domain. The implications for transcription activation by Pho4 are discussed.